Adverse Childhood Experiences in Mexico: Prevalence and Association with Sociodemographic Variables and Health Status - Sánchez Jáuregui, Teresa de Jesús; Téllez López, Arnoldo; Almaraz Castruita, Diana Aracely; Valdez, Arturo; Hinojosa Fernández, Rogelio; García Balvaneda, Hugo; Juárez García, Dehisy Marisol (2023)
Adverse Childhood Experiences (ACEs) refer to a semantic eld of negative childhood events that, in conjunction with insu cient personal, family, or contextual coping resources, have the potential of becoming traumatic.